Vibroacoustic analysis of a clamped finite orthotropic laminated double-composite plate with an air cavity - Thinh, Tran Ich; Thanh, Pham Ngoc (Vietnam Journal of Mechanics, 2019)
The vibroacoustic analysis of a clamped finite orthotropic laminated double-composite plate with a closed air cavity is investigated analytically presented within classical laminated plate theory for laminated composite plate. Using the method of modal decomposition, a double Fourier series solution is obtained to characterize the vibroacoustic performance of the structure. The sound transmission loss (STL) is calculated from the ratio of incident to transmitted acoustic powers. The accuracy of the solution is shown with comparing the STL values obtained from this presented model with the experimental and theoretical results available in literature. The soundproof ability of finite double-composite plate with a clamed boundary is shown. The effects of thickness of faceplates, thickness of air cavity and the angles of the incident sound are systematically examined.